A PSYCHOLOGICAL ANALYSIS OF LITERATURE AND READERS OF THE NOVEL SEKAR RINONCE BY TULUS SETIYADI - Indra Septiawan; Herlina Setyowati; Yuli Widiyono (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2026)
This study aims to describe the literary psychology (id, ego, superego) in Tulus Setiyadi’s novel Sekar Rinonce and the psychology of readers of Tulus Setiyadi’s novel Sekar Rinonce. Methodologically, this study is descriptive and qualitative. Data collection techniques include literature review and interviews. The research instruments were the researcher and the informants, with additional instruments consisting of data recording sheets and relevant literary study books. The data validity techniques used in this study were increased rigor and triangulation. The data analysis technique used content analysis. The data presentation technique used an informal method. The research findings regarding the literary psychology of the novel Sekar Rinonce by Tulus Setiyadi, examined through Sigmund Freud’s psychoanalytic theory of personality, are as follows: (a) the id in the character Yuli in Sekar Rinonce manifests as an outpouring of her emotions when facing problems; (b) the ego in the character Yuli manifests as a means of restraining those emotions; (c) the superego of the character Yuli takes the form of a process of moral reflection and introspection regarding the events that occur. The psychology of readers of Tulus Setiyadi’s novel Sekar Rinonce: (a) cognitive processes in the form of readers’ analysis or understanding of Tulus Setiyadi’s novel Sekar Rinonce; (b) readers’ affective processes in the form of impressions or feelings after reading Tulus Setiyadi’s novel Sekar Rinonce; (c) evaluative processes in the form of moral values that can be derived from Tulus Setiyadi’s novel Sekar Rinonce.